2017
DOI: 10.2147/dmso.s126763
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of type 2 diabetes with glucagon-like peptide-1 receptor agonists

Abstract: Continuously reducing excess blood glucose is a primary goal for the management of type 2 diabetes (T2D). Most patients with T2D require glucose-lowering medications to achieve and maintain adequate glycemic control; however, treatment failure may occur, limiting treatment options. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are an emerging therapeutic class that can be prescribed for patients instead of basal insulin after the failure of oral therapies. Recent studies have focused on the durability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
(58 reference statements)
0
24
0
2
Order By: Relevance
“…Long‐term data with glucose‐lowering therapies for type 2 diabetes are limited, particularly for recently available agents . Most phase 3 clinical studies are 26 or 52 weeks in duration and cannot predict clinical outcomes over several years, although they often have open‐label extensions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Long‐term data with glucose‐lowering therapies for type 2 diabetes are limited, particularly for recently available agents . Most phase 3 clinical studies are 26 or 52 weeks in duration and cannot predict clinical outcomes over several years, although they often have open‐label extensions.…”
Section: Introductionmentioning
confidence: 99%
“…Most phase 3 clinical studies are 26 or 52 weeks in duration and cannot predict clinical outcomes over several years, although they often have open‐label extensions. Among glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs), follow‐up periods have extended to 2 years for albiglutide, dulaglutide and liraglutide and to 7 years for exenatide once weekly (QW) . Whereas cardiovascular outcome trials for the GLP‐1RAs exenatide, liraglutide and semaglutide and the sodium–glucose cotransporter‐2 inhibitors empagliflozin and canagliflozin had relatively long follow‐up periods, patient populations generally comprised those at high cardiovascular risk and were not representative of all patients in real‐world practice …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This defect in insulin secretion is accompanied by a deficit in β-cell mass [1,2]. Recently, a glucagon-like peptide-1 (GLP-1) mimetic class of drugs, widely referred to as incretins, has shown promise as a therapeutic for treatment of T2DM [3,4]. A growing body of evidence has shown that GLP-1 can enhance glucose-stimulated insulin secretion (GSIS) and insulin synthesis, inhibit glucagon secretion, confer glucose sensitivity to glucose-resistant β-cell, stimulate β-cell proliferation and neogenesis and inhibit β-cell apoptosis [5][6][7].…”
mentioning
confidence: 99%